(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the essential role of verbs in language and their grammatical categories, emphasizing their importance in sentence construction and meaning. It provides a comprehensive breakdown of key categories, including tense, aspect, mood, voice, person, number, transitivity, and the use of auxiliary and modal verbs. The explanations are detailed yet accessible, making complex grammatical concepts easy to grasp. The dual conclusions highlight both the technical significance of verbs and their broader impact on effective communication. This piece serves as a valuable resource for language learners, educators, and anyone interested in understanding the intricacies of grammar.